P137 An audit to check the awareness among paediatric NCHD about documentation of childhood development in clinic letters in wexford general hospital. (June 2019) - Zia, Muhammad; Shori, Naeem; Jawad, Muhammad; Azam, Muhammad
Abstract : Introduction: Development is the period of physical, cognitive and social growth that begins at birth and continues through childhood. Between 1–3% of children suffer from global delay. Maximum development occurs in the first two of years of life .Early recognition of developmental issues is important to have a better outcome, appropriate referral and involvement of other services. Aim: Aims of the audit is to see the awareness among NCHD(non consultant hospital doctors) towards development assessment and documentation in clinical letters of patients coming to clinic from Jan 2018 to July 2018. Methodology: Retrospective audit was done from January 2018 to July 2018. A Proforma was designed and random clinic letters of patients attending paediatric clinic were screened for documentation of all six areas of childhood development (gross motor, fine motor vision, hearing, speech and language and social) seen by NCHD. Results: Total 70 patients were included in the audit. 45 male and 55 female patients. Age range varies from 3 months to 13 years. 35 (50%) of the patients were below 5 years of age. Childhood development was mentioned in 30(43%) of patients. 40 (57%) patients have no records of being screened for appropriate age related developmental milestones. Out of 70 only 6 patients (8%) have their proper documentation about the development indicating all six areas of development. Regarding different areas of development documentation was as follows: Gross motor 14(20%) Fine motor 10(14%) Vision 07(10%) Speech 12(17%) Hearing 06(08%) Social 11(15%) Conclusion: Developmental assessment is a neglected area in general paediatrics clinic settings. Outcome about the documentation of general paediatric development assessment was very poor as 57% of the patients have no records of any development assessment in clinic. Recommendations: Awareness should be raised among NCHDs about the importance of developmental assessment in children coming to clinic. A regular training session for new doctors about routine developmental screen at the start of rotation may be helpful. There should be a brief developmental check list and clinic letter layout displayed in clinic area settings. More opportunities should be given to NCHDs to attend developmental clinics